PROGRAM KAMPUS MENGAJAR SEBAGAI INISIASI PENINGKATAN ASESMEN KOMPETENSI MINIMUM DI SULAWESI TENGAH - Putra, Exsa; Alya Aprilia Ticoalu, Inneke (Jurnal Samudra Geografi, 2024)
Abstract: The Teaching Campus Program is one of the policies produced by the Ministry of Education and Culture with the main aim of improving the quality of education in Indonesia. The aim of this Teaching Campus activity is to find out how far the implementation of the program from the Class 5 Teaching Campus is an embodiment of contributing to learning while having an impact. Students as agents of change can help the quality of education on a national and international scale. AKM (Minimum Capability Assessment) is a government policy as a substitute for the National Examination (UN) where the AKM concept is useful for measuring students' literacy and numeracy skills as well as understanding of the use of technology. Analysis of answers based on the two tables above between the pre-test and post-test in literacy increased by a difference of 8%, while in numeracy there was a drastic decrease with a difference of 28%. This shows that students lack understanding regarding numeracy, so efforts are needed to improve student numeracy at SD Inpres 3 Talise. Implementation of the Class 5 Teaching Campus Program in implementing and guiding technology adaptation at SD Inpres 3 Talisehas been achieved in accordance with the objectives of the Teaching Campus Program, where students and teachers will be able to optimize the use of technology.